DETERMINANTS OF DIVIDEND PAYOUT POLICY: A CASE OF PROPERTY, REAL ESTATE, AND BUILDING CONSTRUCTION SECTOR - Wardono, Anindita Alifa; Murtaqi, Isrochmani (Journal of Business and Management, 2018)
Abstract. Dividend payout policy is an important decision both for investor and corporation. There are several different theories and opinions related with dividend payout policy. Therefore, this research aims to find the determinant factors of dividend payout policy for firms engage in Indonesian property, real estate, and building construction sector. This research belongs to quantitative research. Panel data regression with fixed effect model as the approach is employed as the method to analyze the data. The sample consists of 18 companies from year 2013-2016 and taken using purposive sampling method. This research found that there is significant positive relationship between leverage and dividend payout ratio. All the independent variables also found simultaneously affect dividend payout ratio. The implication of this study is that leverage should be the factor that investors and the company should pay more attention related with the information of dividend payout policy of the company. Keywords:  Dividend payout ratio, firm size, leverage, liquidity,  regression analysis